2014
DOI: 10.1186/2052-1839-14-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and severity of anemia among school children in Jimma Town, Southwest Ethiopia

Abstract: BackgroundAnemia is a major health problem worldwide. Because of health and socioeconomic problems, the prevalence of anemia is higher in developing countries. Children and pregnant women are the most vulnerable groups to anemia. The aim of the present study was to determine the magnitude of anemia among school children.MethodsA cross-sectional household survey was conducted in January 2011 on 423 children, aged 6–14 years, selected through systematic random sampling method. Sociodemographic and anthropometric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
67
8
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(97 citation statements)
references
References 19 publications
21
67
8
1
Order By: Relevance
“…This figure is consistent with previous reports in southern Islamic Republic of Iran (9-12), but is lower or higher than the prevalence found in other developing countries (13,14). The prevalence of iron-deficiency anaemia in developed courtiers has declined in recent decades, but there has been little change in developing countries.…”
Section: Data Collectionsupporting
confidence: 91%
“…This figure is consistent with previous reports in southern Islamic Republic of Iran (9-12), but is lower or higher than the prevalence found in other developing countries (13,14). The prevalence of iron-deficiency anaemia in developed courtiers has declined in recent decades, but there has been little change in developing countries.…”
Section: Data Collectionsupporting
confidence: 91%
“…Assefa et al have reported a prevalence of 37.6% in their study of adolescent girls, which was slightly lesser than current study. 10 Out of which, 18.1% and 19.6% had mild and moderate anaemia respectively, but in the current study major proportion of anemia was mild. In study by Chaudhary et al 4 35.1% of the adolescent girls had anemia.…”
Section: Discussionmentioning
confidence: 86%
“…In study by Assefa et al the factors, which were associated with presence of anaemia were low family income, poor maternal education, and vegetarian diet. 10 Chaudhary et al have reported socio-economic status and literacy status of parents. 5 As the key factors associated with anemia.…”
Section: Discussionmentioning
confidence: 99%
“…These high rates were similar to the observations from previous studies 5, 6,11 . Assefa et al 16 also reported anaemia prevalence of 30.1% among 12-14 year old school children in Ethiopia. VAD (42.22%) has also been reported among school going adolescents 17 .…”
Section: Discussionmentioning
confidence: 99%